The Effect of Working Capital Management on Profitability in Companies listed on the Tehran Stock Exchange - Seyed Mojtaba Kavoosi Davoodi; Yasin Seraj; Zeynab Esmaili Dehkalani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The present study aims to assess the effect of working capital management on the firm's profitability in the companies listed on the Tehran stock exchange. Methodology: The study sample comprised 125 companies studied between 2014 and 2019. In this study, the variable "net income before deducting interest and taxes to total assets" as a measure of the profitability of the variables, the period of collection of receivables, inventory turnover period as capital management criteria in circulation in variables, firm size, sales growth, the ratio of current assets to current liabilities ratio of financial debt to total assets and operating profit were used as the control variable. Findings: This study showed a significant inverse relationship between the profitability of companies with receivables collection periods and those with inventory turnover periods. Managers can reduce the period with the debt collection company to stay within reasonable limits and increase profitability. Originality/Value: It is expected that companies, using proper management of working capital, take steps to increase the company's value and thus increase its shareholders' wealth.